CPC-120 Ranitidine-Induced Systemic Hypersensitivity Reaction: A Case Report. (12th March 2013) - Geneste, M; Bourget, S; Brun, P; Dufrene, I; Hida, H
Abstract : Background: Ranitidine is a histamine-2-receptor antagonist (antiH2) widely used with an excellent safety record. It's a drug included in the premedication for several chemotherapy regimens. Purpose: To report a case of hypersensitivity to ranitidine. Materials and Methods: Case report, literature review. Results: A 68-year-old man was being followed at hospital for management of metastatic lung carcinoma. A third-line treatment with weekly paclitaxel had been decided. The usual premedication includes intravenous ondansetron, ranitidine, dexchlorpheniramine and methylprednisolone. The patient's anamnesis hadn't reported any allergic events. During the first course, the patient presented pruritus 5 minutes after ondansetron and ranitidine injections. Hypotension and warmth occurred despite the administration of dexchlorpheniramine. 120 mg of methylprednisolone resolved the hypersensitivity completely before the patient received paclitaxel, without further event. During the next course, ondansetron was replaced by metoclopramide. During the ranitidine infusion the patient presented sweats, hypotension and bronchospasm. Ranitidine infusion was stopped and methylprednisolone overcame the reaction. The patient's condition allowed paclitaxel administration although he refused dexchlorpheniramine. The need for antiH2 and the most appropriate premedication for the next courses were discussed by the clinician and pharmacist. Hypersensitivity reactions are reported in ranitidine's SPC with an estimated rare frequency and also in the literature review. A case also reported a cross-reaction between antiH2 and other antihistamines [1], while another author excluded it [2]. As no allergic investigation has been performed, all antihistamines have been removed as a precaution. For subsequent courses the premedication included metoclopramide 10 mg and methylprednisolone 80 mg. No other incidents have been reported. This search didn't formally establish the need for antiH2 in paclitaxel premedication. Conclusion: This case has been reported to the pharmacovigilance centre and reminds clinicians that even commonly used and generally well-tolerated substances can cause serious side effects. References: Thurot-Guillou C et al, Anaphylactic reaction to ranitidine and dexchlorpheniramine. Aouam K et al, Severe ranitidine-induced anaphylaxis: a case report and literature review. No conflict of interest.